Households’ demand for disaggregated meat products in Sri Lanka: A Censored Quadratic Almost Ideal Demand System Model - Musthifa, B.; Sivashankar, S.; Sooriyakumar, K.; Sarujan, S. (Wayamba University of Sri Lanka, 2025)
The economic crisis and increased prices for essential goods have severely affected consumption patterns of meat products in Sri Lanka. Therefore, this study aims to estimate demand for disaggregated meat products. This study used the data from Household Income and Expenditure Survey-2019 and employed the Quadratic Almost Ideal Demand System model to estimate the own-price, cross-price, and expenditure elasticities for different meat products, including beef, mutton, chicken, pork, and sausage. To correct the zero-consumption, the consistent two-step estimation procedure was used. The findings of this study revealed that all the meat products considered in this study are normal goods; however, beef (1.202) and chicken (1.076) are more sensitive to changes in expenditure than mutton (0.692), pork (0.609), and sausages (0.456). Also, own-price elasticities indicated that mutton (-3.491), beef (-1.993), sausages (-1.551), and chicken (-1.073) have elastic demand, while pork (-0.789) has inelastic demand. Notably, results denoted that mutton is highly sensitive to price changes than other meat products in this study. The estimated cross-price elasticities exhibit substitute and complementary relationships between meat products; however, mainly substitute relationships are identified among them. The results suggest that chicken, beef, and pork are substitutes for each other. Further, the cross-price elasticities show that sausages are substitutes for chicken and mutton, while complements for beef and pork. Therefore, the findings of this study will assist policymakers and marketers in understanding how Sri Lankan households will react to changes in price and expenditure on various meat products.
Keywords: Choice modelling; Conditional logit model; Sustainable lagoon eco system management